REDUCTION OF ACCOUNTS RECEIVABLES AS A METHOD OF MANAGING THE FINANCIAL SECURITY OF ENTERPRISE’S AUTOSANATION - Яцюк, Олег (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The article examines the peculiarities of managing the financial support of autosanation procedures by reducing the company’s accounts receivables. It has been established that in Ukrainian and foreign scientific and applied literature there is no adequate coverage of the issues of using methods of reducing accounts receivables as a source of enterprise’s autosanation financing. The author justifies the urgency of solving the remaining problem by the fact that the timely repayment of accounts receivables, liquidation of the overdue part of it is a vital problem for all enterprises, and especially those that are in a state of crisis and need financial resources to carry out autosanation measures. The author selects out three main directions of increasing the liquidity of accounts receivables (transfer of accounts receivables directly into cash, transfer of accounts receivables into more liquid assets with the aim of their further conversion into cash, reduction of accounts receivables with a simultaneous reduction of the company’s liabilities), in accordance with which specific measures to increase the liquidity of accounts receivables are grouped and analyzed, the peculiarities of their application in practice are considered. The main methods of managing the financial support of autosanation procedures at the expense of reducing the company’s accounts receivables considered by the author include factoring, forfeiting, accounting for promissory notes, early repayment of the debt by the debtor, receiving a part of the debtor’s liquid assets for the repayment of the accounts receivables, conversion of the accounts receivables into packages of the debtor’s shares, bilateral offsetting of the accounts receivables debts, multilateral netting of accounts receivables, transfer of debt to the debtor, assignment of claims and assignment of the contract. Thus, in the work, the author grouped the sources of financing for the company’s autosanation due to the increase in the liquidity of accounts receivables and analyzed them in detail. It is noted that for effective financial support of autosanation procedures due to the reduction of accounts receivables at the enterprise, it is necessary to implement measures aimed at improving the quality of management of accounts receivables of business entities.